Tea Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
HS-1058, a 6-page fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides homeowners with a basic reference for growing tea in the home landscape. Tables include suggested cultural practices by month and nutritional values. Published by the UF Department of Horticultural Sciences, November 2005.